The Power of Delay: Banking System Structure and Implementation of the Basel Accords. (March 2022) - Mitchell, Christopher
Abstract: Recent developments in the international banking system, especially the 2007–9 crisis and subsequent wave of postcrisis regulation, have drawn increasing attention to the structural power of banks and banking systems. States need a functioning financial system to ensure the overall health of their economies, so states must shape policy to protect their financial firms. National financial systems may be dominated either by banks or by capital markets. In states where banks dominate provision of capital, states must shape policy to protect their banks because of their structural importance, independent of any lobbying or other direct action on the part of banks to exercise instrumental power. The entangling of structural and instrumental power means studying differences in structural power requires either careful case-study work or cross-national comparison of responses to a common shock. The implementation of the 2011 Basel III Accords provides just such an opportunity. This article offers a quantitative analysis of a new dataset of implementation of Basel III components in the Basel Committee on Banking Stability member states from 2011 to 2019 and demonstrates the structural power of banks in bank-based systems to accelerate implementation of favorable policies and slow implementation of unfavorable ones.